A Content Analysis of Sexual Consent and Refusal Communication in Mainstream Films. Issue 6 (24th July 2019) - Jozkowski, Kristen N.; Marcantonio, Tiffany L.; Rhoads, Kelley E.; Canan, Sasha; Hunt, Mary E.; Willis, Malachi
Abstract : Young adults have limited access to comprehensive sex education. As such, they may seek sexuality information through such alternative sources, such as mass media. Previous research suggests that media, including films and television shows, can influence sexual behaviors and attitudes. Because sexual consent communication is important to sexual experiences, the purpose of this study was to assess how sexual consent and refusal communication were depicted in films. We also examined contextual factors that influence consent and refusal communication, such as gender, relationship status, location, and types of sexual behaviors. Four researchers analyzed popular mainstream films (N = 50) from 2013 based on a codebook developed inductively and deductively. The most common consent and refusal communication cues were nonverbal or implicit. The majority of scenes portrayed consent immediately before sexual activity. We also conducted chi-squared analyses to assess differences in consent and refusal communication based on gender and relationship status. There were no gender differences in the portrayal of consent cues; however, characters in established relationships used nonverbal cues more often than those in novel relationships. Mass media can normalize behaviors, and our results suggest that films may further normalize nonverbal or implicit consent cues.